Recruitment Practices in Times of Demographic Change: The Case of Japan - Hennings, Matthias; Pilz, Matthias; Bebenroth, Ralf (International journal of training and development, 2025)
ABSTRACT Due to a shrinking number of employable graduates, companies in industrialised nations have increasingly faced problems in hiring qualified young people. This situation is particularly pronounced in Japan, where companies are competing for the best talents. Based on a multi‐stakeholder perspective, this study examines changes in the Japanese recruitment system from the viewpoint of companies, university career centres and external organisations involved in recruitment. Using in‐depth interviews with these stakeholders, this study investigates how recruitment practices in Japan have changed, which guidelines for recruitment are currently followed by companies, and to what extent traditional recruitment practices still prevail. As the results show, recruiting activities in Japan have accelerated over the last years with companies trying to recruit university students early in their studies to secure qualified talents. This article also discusses the implications of these findings for Japan and other industrialised countries with similar demographic problems.